Occurrences of Dental Diseases in Dogs in a Teaching Animal Hospital, Morogoro, Tanzania - Justine, Immanuel; Makungu, Modesta (Journal of Biology and Life Science, 2024)
Dental diseases are common in dogs with a prevalence of more than 80% in some breeds of dogs. They cause damage to oral health and may act as a source of bacteria causing other diseases such as endocarditis, pneumonia and arthritis. A cross section study was conducted to determine the current status on the occurrence of dental diseases in dogs attended at Sokoine University of Agriculture (SUA) Teaching Animal Hospital in Morogoro, Tanzania. A total of 87 dogs were examined macroscopically for the presence of dental diseases. Dogs examined in this study ranged from medium (93.1%) to large (6.9%) sized, and up to 73.6% were mixed-breed. The minimum and maximum ages of the dogs were 6 and 72 months, respectively, with majority being females (60.9%). The proportions of intact, spayed and castrated were 92%, 5.8% and 2.3%, respectively. Of the 87 dogs examined, 62.1% had different kinds of dental diseases. The frequently observed dental diseases were; dental deposits (43.7%), missing teeth (24.1%), periodontal disease (20.7%), dental attrition (16.1%), and dental abrasion (10.3%). Further, it was noted that none of the dogs had been previous underwent routine dental check-up or anaesthetised for dental cleaning. This study indicates that dental diseases are frequent in dogs attended at SUA Teaching Animal Hospital. Therefore, it is recommended that routine dental examination should be performed in dogs presented at the Teaching Animal Hospital. Further, there is a need for educating dog breeders and owners on the importance of dental home care.